Pairs trading. - Tan, Lee Kwang. (2011)
In this research project, we examine the possibility of reaping excess profits by adopting the Pairs Trading strategy in the Singapore stock market, using historical data from January 2004 to March 2010. We derived a sample of 1,957 pairs which we subjected to 20 research and implementation periods, giving us a total of 39,140 experimental results.